COMMUNICATION STRATEGIES FOR SUPERVISORS IN IMPROVING THE PROFESSIONAL ABILITY OF TEACHERS AT MADRASAH IBTIDAIYAH NEGERI 15 LANGKAT - Candra Wijaya; Haidir Haidir; Zainal Arifin (Universitas Dharmawangsa Medan, 2020)
this study was to determine: 1) the communication strategy of supervisors in improving the professionalism of teachers at Madrasah Ibtidaiyah Negeri 15 Langkat; 2) The media used by supervisors in carrying out communication at Madrasah Ibtidaiyah Negeri 15 Langkat; and 3) Supporting and inhibiting factors for Supervisory Communication Strategies in increasing the professionalism of teachers at Madrasah Ibtidaiyah Negeri 15 Langkat.This thesis research uses a qualitative approach with descriptive methods. The collection techniques used interview, observation and documentary studies, while to strengthen the validity of the data findings and the authenticity of the research, the researcher referred to the use of data validity standards consisting of creadibility, transferability, dependability and comfirmability. The results of this study are: 1) supervisory communication strategies in increasing the professionalism of teachers at MIN 15 Langkat in the form of interpersonal techniques with open, informative, persuasive, educational and instructive; 2) The media is used by supervisors in carrying out communication at Madrasah Ibtidaiyah Negeri 15 Langkat in addition to holding face-to-face communication also using information communication technology (ICT) using the WhatsApp application by creating a group for 15 Langkat Madrasah, this media is considered quite effective in carrying out madrasah development activities as a whole, including specifically the principal and teachers; and 3) Supporting factors for the effectiveness of supervisory communication strategies in increasing the professionalism of teachers due to the emergence of a good sense of togetherness and kinship so far. This sense of togetherness and kinship makes a strong bond in the communication process in madrasas and there are no significant obstacles in communicating with supervisors.